An atypical case of rhinosporidiosis: a case report - C. J., Timna; D., Chandrika (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Rhinosporidiosis is an infective chronic granulomatous lesion caused by an organism rhinosporidium seeberi, which is seen endemic in some parts of Asia. This organism is difficult to culture and the diagnosis is based on histopathological examination. This disease is more commonly seen in men, in second to third decade.. This case report is regarding a case of a 55 years old lady with history of recurrent rhinosporidiosis in nose. The lesion was found to arise from the inferior meatus and was pale smooth glistening in appearance, insensitive and does not bleed on touch. Site of origin of the polyp and the appearance was atypical of that of rhinosporidiosis. Patient was subjected for endoscopic excision and cauterisation of the base of the lesion and sent for histopathological examination .Biopsy confirmed the diagnosis of rhinosporidiosis.